2020
DOI: 10.1186/s12909-020-1945-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported confidence in patient safety competencies among Chinese nursing students: a multi-site cross-sectional survey

Abstract: Background: Nursing interns are an important backup force for nursing professionals, so efforts to strengthen their patient safety (PS) competencies are a major priority. To do so requires assessing the strengths and weaknesses of Chinese nursing students' PS competence and identifying the influencing factors. Methods: This was a multi-site, cross-sectional, web-based study that was carried out between September 2018 and January 2019. A national online survey was completed by 732 Chinese undergraduate nursing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
38
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 26 publications
14
38
3
Order By: Relevance
“…In thıs study, overall, students reported that they were more confident in their knowledge about patıent safety gained in the classroom setting than in the clinical setting. These findings are similar to some studies [37,38,44,46,61,65,66], although other studies reported mixed results, with reported clinical scores being higher than the class scores in more than half of the dimensions [9,45,65]. Classroom ıs perceived as a safe environment of learning about working in multi-professional teams, understanding the system-based nature of patient safety problems [50] and being more confıdent to speak up [66,67].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In thıs study, overall, students reported that they were more confident in their knowledge about patıent safety gained in the classroom setting than in the clinical setting. These findings are similar to some studies [37,38,44,46,61,65,66], although other studies reported mixed results, with reported clinical scores being higher than the class scores in more than half of the dimensions [9,45,65]. Classroom ıs perceived as a safe environment of learning about working in multi-professional teams, understanding the system-based nature of patient safety problems [50] and being more confıdent to speak up [66,67].…”
Section: Discussionsupporting
confidence: 87%
“…Students valued learning about patient safety on the technical aspects higher than the sociocultural aspects in both settings. The findings are consensus to other studies [44][45][46]. That indicates that a system-based approach is not realised by the students during their education [42,51], as they are not engaged in learning the organisational strategies and systems in the clinical setting [39,42].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Findings corroborate a study of about patient safety competencies of undergraduate nurses in 7 Chinese administrative provincial regions (Huang et al, 2020). In another research, it affirmed a previous study of in Thailand about self-rated nursing competency.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to another study conducted by Nabilou et al, (2015), the nursing and midwifery students dedicated more knowledge to patient safety than medical students. The latest study also revealed that nursing students in China gain more knowledge in the clinical setting and manage gaps in their knowledge (Huang et al, 2020). This condition will become more efficient by fostering collaboration between nursing faculty and clinical nurses to teach patient safety content to close the knowledge gap in theory and practice (Huang et al, 2020).…”
Section: The Level Of Knowledge Regarding Patient Safetymentioning
confidence: 99%